Students' perception on sexual on sexual harassment (Journal of the Philippine Association for Technology in Home Economics in State Colleges and Universities, Inc., 2001)
This study aimed to determine the perception of students on sexual harassment, and evaluate the clothing styles perceived to contribute to sexual harassment. The respondents were 101 female and three male students from the College of Home Science and Industry, Central Luzon State University, Munoz, Nueva Ecija. A 5-point Likert scale instrument developed by the researcher was used to analyze the data. Out of the 104 respondents, 20 female students indicated that they experienced sexual harassment in the classroom. The clothing styles perceived to contribute to sexual harassment are: low cut neckline attire followed by see-through dress, mini length skirt and fitted pants. When asked what they will do when they experience sexual harassment, most of the respondents answered that they will confide first with their classmates, then tell their parents and finally, the authority. The school must formulate policy to intensify campaign against sexual harassment; observe strict guidance and counseling to both students and teachers; and implement appropriate dress code for both teachers and students.